Visceral adiposity index in older adults:Associations with physical functions and cardiometabolic risk - Mohamad Fauzi, Nor Farah; Che Hasan, Muhammad Kamil; Henry Joseph, Leonard (Wiley Online Library, 2014)
Studies have shown that visceral adiposity index (VAI) reflects metabolic disturbances and cardiometabolic risk, both of which are associated with lower physical functions. This study aimed to evaluate the associations of VAI with physical functions (i.e. cardiorespiratory fitness, balance, grip strength) and cardiometabolic parameters in older adults. Sixty, physically inactive men and women (n male = 35, age: 60.2 ± 4.4 years, BMI: 28.8 ± 4.6 kg/m2), underwent (1) anthropometric measurements; (2) 6-minute walk test, timed up-and-go and hand grip tests; (3) assessment of plasma insulin, glucose, triglycerides, HDL, adiponectin, and highsensitivity C-reactive protein (hs-CRP). VAI was estimated using anthropometric (BMI and waist circumference) and biochemical (triglycerides and HDL) parameters. Insulin resistance was calculated as HOMA-IR index. Partial correlations analysis controlled for gender demonstrated positive associations for VAI with insulin resistance (r = 0.658, p < 0.001) and hs-CRP (r = 0.325, p = 0.012). No association between VAI and physical function parameters was observed. In addition, waist circumference was inversely correlated with plasma adiponectin (r = −0.297, p = 0.023). Multivariate regression analysis revealed that only insulin resistance was an independent predictor of VAI. This study suggests that VAI is a strong indicator of deterioration in insulin sensitivity, and is associated with hs-CRP but not physical functions in older adults.